Penetrating Foreign Bodies in Head and Neck Trauma: A Surgical Challenge. Issue 3 (September 2018) - Voss, JanOliver; Thieme, Nadine; Doll, Christian; Hartwig, Stefan; Adolphs, Nicolai; Heiland, Max; Raguse, Jan-Dirk
Penetrating foreign bodies of different origins in the head and neck are rare and potentially dangerous injuries, which might pose problems for their detection, primary care, and final treatment. Depending on the severity of the underlying trauma, some injuries present a higher risk for the presence of foreign bodies. Minor wounds, including common lacerations, are likely to be contaminated with loose gravel debris or dental fragments, and need to be distinguished from severe wounds caused by impalement, shootings, stabbings, and explosions. Blast injuries resulting from terror attacks are challenging recent therapeutic concepts. Even though these injury patterns are uncommon, they carry the risk of impacted objects with dramatic consequences. Despite improving medical imaging techniques, detection remains a challenge as it is dependent on the material of the foreign body, the affected anatomical site, and the injury severity. Therefore, a detailed history of the circumstances leading to trauma is essential when foreign objects are not visible during clinical examination. Precise detection of the foreign body, its anatomical position, and the affected surrounding structures are vital, especially for impalement injuries of the head and neck area. Therefore, an interdisciplinary planning approach is essential prior to removal of the foreign object. Finally, tension-free anatomical adaptation of the corresponding structures is crucial for maintaining and restoring aesthetic and function. Here, we give an overview of the diagnosis and treatment of cases of foreign body injuries encountered in our department.